ANALISIS KINERJA KARYAWAN PT. PUTRA KEDIANGAN PROPERTINDO - Irianto Loka; Mahalayati - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
This study is categorized as a census study. The type of data in this study is quantitative ornumerical data. The instrument of this study using questionnaire. Population and sample in thisresearch is all employees of PT. Putra Kediangan Propertindo of 32 employees. Sampling technique inthis study using simple random sampling. Test the validity of the instrument using Confirmatory FactorAnalysis while the reliability test using Alpha Cronbach. Measurers proved to be valid and reliable forresearch instruments. Multiple regression analysis was used to test the hypothesis of this study.The results of research at the level of significance of 5% found that: (1) Job satisfaction has apositive and significant impact on employee performance PT. Putra Kediangan Propertindo, it is shownby the acquisition of t test 2.070 with significance of 0.47. (2) Load work does not significantly affect theperformance of employees of PT. Putra Kediangan Propertindo. This is shown by the acquisition of ttest 0.421 with significance of 0.677. (3) Job satisfaction and workload simultaneously have nosignificant effect on employee performance of Putra Kediangan Propertindo, it is marked from theacquisition of F test obtained F arithmetic 2,152 with significant level (p) 0,134a. The equation ofemployee performance variation determined by job satisfaction and workload is 12,9 percent (R sequare= 0,129). R square number is 0,129 this means equal to 12,9% employee performance influenced byjob satisfaction variable and work load. While the remaining 87.1% influenced by other factors outsidethis research variable.